1999
DOI: 10.1097/00005537-199912000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α‐Toxin of Staphylococcus aureus on the Ciliary Activity and Ultrastructure of Human Nasal Ciliated Epithelial Cells

Abstract: CBF increased at first, but with increasing incubation time ciliary movements decreased gradually and stopped eventually. This loss of CBF may be an irreversible change associated with ultrastructural changes in the mitochondria and the plasma membrane of the cilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Hla expression is Agr-dependent and increased upon interaction with epithelial cells, infection in vivo, and is higher in USA300 strains [3, 19, 32, 74]. In airway epithelial cells α-hemolysin has been associated with calcium fluxes, pro-inflammatory signaling [75], and alteration of ciliary beat frequency of cells (Fig. 2) [76].…”
Section: α-Hemolysinmentioning
confidence: 99%
“…Hla expression is Agr-dependent and increased upon interaction with epithelial cells, infection in vivo, and is higher in USA300 strains [3, 19, 32, 74]. In airway epithelial cells α-hemolysin has been associated with calcium fluxes, pro-inflammatory signaling [75], and alteration of ciliary beat frequency of cells (Fig. 2) [76].…”
Section: α-Hemolysinmentioning
confidence: 99%
“…While there is now clear evidence that the cystic fibrosis transmembrane conductance regulator (CFTR), which had been previously implicated with release of ATP from airway epithelial cells [19], does not provide an exit pathway for ATP [20,21], pannexin channels, specifically Panx1, have been shown to serve as potential exit pathways for ATP in stressed cells [22,23,24,25]. Alternatively, cell stress induced by exposing cells to pore-forming toxins, such as α-toxin, may result in alterations in mitochondrial integrity and reduction of ATP production, which may contribute to lowering cellular ATP content [26,27]. Thus, it is still unclear whether ATP production is attenuated in toxin-exposed cells or ATP gets lost from the cytosol to the external space through the Hla pore or other pathways that may be activated by signals elicited by attachment of Hla monomers or pore formation.…”
Section: Introductionmentioning
confidence: 99%
“…More than one-third of the general population (37.2%) are carriers of Staphylococcus aureus in the nasal cavity [3], this organism is frequently isolated in chronic rhinosinusitis [4]. It is known that bacterial toxins reduce mucociliary transport, and alpha-toxin causes acute rhinosinusitis [5,6]. It has been demonstrated that exotoxins secreted by colonizing S. aureus are capable of triggering the inflammatory infiltrate characteristic of chronic rhinosinusitis with nasal polyp [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that exotoxins secreted by colonizing S. aureus are capable of triggering the inflammatory infiltrate characteristic of chronic rhinosinusitis with nasal polyp [7,8]. Previous studies indicate that exotoxins produced by bacteria can decrease ciliary activity, subsequently inducing acute rhinosinusitis [6,9].…”
Section: Introductionmentioning
confidence: 99%